Re-irradiation for local primary-recurrence esophageal squamous cell carcinoma treated with IMRT/VMAT - Geng Xiang; Chunsheng Xu; Guangjin Chai; Bo Lyu; Zhaohui Li; Bin Wang; Mei Shi; Lina Zhao (Radiation Oncology, 2023)
Abstract Purpose Local primary-recurrence of esophageal squamous cell carcinoma (ESCC) after definitive treatment has the potential for increasing overall survival with re-irradiation (Re-RT), especially with advanced technique. This study aimed to evaluate the efficacy and toxicities of Re-RT using intensity-modulated radiotherapy (IMRT)/volumetric modulated arc therapy (VMAT) for local primary-recurrence of ESCC. Materials and methods A total of 130 ESCC patients with local primary-recurrence from Xijing hospital between 2008 and 2021 were enrolled and 30 patients underwent IMRT/VMAT based salvage Re-RT. Cox regression analysis was used to analyze the prognostic factors for overall survival (OS) and after recurrence survival (ARS). The toxicities of 30 patients receiving Re-RT were also assessed. Results The median OS and ARS of the 130 recurrent patients were 21 months (1−164 months) and 6 months (1−142 months). The 1-, 2-, and 3-year OS rates were 81.5%, 39.2%, and 23.8%, respectively. Besides, the 1-, 2-, and 3-year ARS rates were 30.0%, 10%, and 6.2%. Multivariate analysis showed that Re-RT ± chemotherapy (p = 0.043) and chemotherapy alone (p < 0.001) and esophageal stents (p = 0.004) were independent prognostic factors for OS. The median OS of 30 patients treated with Re-RT were significantly better than that of 29 patients treated with chemotherapy (34.5 months vs. 22 months, p = 0.030). Among 30 ESCC patients treated with Re-RT, the median OS and ARS were 34.5 months (range 12–163 months) and 6 months (range 1−132 months), respectively. The recurrence-free interval (RFI) (> 12 months) and initial radiation dose (> 60 Gy) were significantly associated with improved OS. Radiation esophagitis (Grade 1–2) occurred in 16 patients and myelosuppression (Grade1−2) occurred in 10 patients. Grade 3 toxicities (radiation esophagitis and myelosuppression) were only 13.3%. There were no grade 4 toxicities. Conclusion Our results demonstrated that IMRT/VMAT-based Re-RT was an effective therapeutic option for ESCC patients with local primary-recurrence compared with chemotherapy alone or without any treatment. Re-RT had improved OS but unfavorable ARS.